Implementasi Integrated Marketing Communication Local Agency (Friendshub) dalam Membangun Brand Awareness - Amanda Noviyanti; Oktaviana Purnamasari (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to examine how the implementation of Integrated Marketing Communication (IMC) carried out by Friendshub contributes to building and strengthening brand awareness. Employing a descriptive qualitative approach and a case study method, data were collected through in-depth interviews with the core team of Friendshub and documentation of marketing activities, which were then thematically analyzed to explore communication patterns and creative strategies applied. The findings reveal that Friendshub integrates six elements of IMC as proposed by Belch and Belch (2021)—advertising, sales promotion, public relations, personal selling, direct marketing, and digital/interactive marketing—implemented across various channels such as social media, WhatsApp, email blasts, and event organization that emphasizes direct experiential engagement. The success of this implementation is supported by close communication with clients, consistent visual identity, and the adaptability of messages to audience needs, while challenges include limited budgets, dependence on client briefs, and short execution timelines. These findings highlight that consistent, creative, and adaptive IMC practices are not only effective in enhancing brand awareness but also in strengthening long-term relationships between Friendshub as a brand and its audience, thereby contributing positively to the sustainability of its image and corporate growth.